Implementasi Sistem Informasi Manajemen untuk Efisiensi Lembaga Pendidikan Islam - Gugun Gunara; Gilang Fajar; Nuraini (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the implementation of Management Information Systems (MIS) to enhance the efficiency of Islamic educational institutions. Using a qualitative method with a literature review approach, this research analyzes relevant sources on MIS practices in the academic context. The findings indicate that MIS effectively automates the management of student and teacher data, attendance, curriculum, scheduling, and financial reporting, resulting in faster, more accurate, and more transparent administrative processes. The main challenges in implementation include technological readiness, human resource competence, and the need for a gradual deployment strategy. Overall, MIS plays a significant role in improving the quality of management within Islamic educational institutions when supported by adequate organizational preparedness and user training. Keywords: Management Information System, administrative efficiency, Islamic education, literature review.